Psychopathology : foundations for a contemporary understanding - Maddux, James E.; Winstead, Barbara A. (New York : Routledge, 2019)
Psychopathology, Fifth Edition is the most up-to-date text about the etiology and treatment of the most important psychological disorders. The chapters are written by leading experts in the field of psychopathology who provide up-to-date information on theory, research, and clinical practice. The book is unique in its strong emphasis on critical thinking about psychopathology as represented by chapters on such topics as culture, race, gender, class, clinical judgment and decision-making, and alternatives to traditional categorical approaches to understanding psychopathology. The contributors have incorporated information about and from the World Health Organization's International Classification of Diseases along with information about and from the DSM-5. As with the previous editions, this book remains a true textbook in psychopathology. Unlike the many weighty volumes that are intended as reference books, Psychopathology, Fifth Edition has been designed specifically to serve as a textbook on psychopathology for graduate students in clinical and counseling psychology programs and related programs such as social work. It will also serve as an extremely useful reference source for practitioners and researchers.
Thinking about psychopathology -- Conceptions of psychopathology : a social constructionist perspective / James E. Maddux, Jennifer T. Gosselin, and Barbara A. Winstead -- Psychopathology: a neurobiological perspective / Daniel Tranel, Molly Nikolas, and Kristian Markon -- Developmental psychopathology : basic principles / Janice Zeman, Cynthia Suveg, and Kara West -- Cultural dimensions of psychopathology : the social world's impact on mental disorders / Steven Regeser López and Peter J. Guarnaccia -- Gender, race, and class and their role in psychopathology / Barbara A. Winstead and Janis Sanchez-Hucles -- Classification and diagnosis : historical development and contemporary issues / Thomas A. Widiger -- Psychological assessment and clinical judgment / Howard N. Garb, Scott O. Lilienfeld, and Katherine A. Fowler -- Psychotherapy research / Rebecca E. Stewart and Dianne L. Chambless -- Common problems of adulthood -- Anxiety disorders and obsessive-compulsive and related disorders / Shari A. Steinman, Amber L. Billingsley, Cierra B. Edwards, Mira D. Snider, & Lauren Hallion -- Trauma- and stressor-related disorders / Lori A. Zoellner, Belinda Graham, and Michele Bedard-Gilligan -- Depressive disorders and bipolar and related disorders / Lauren B. Alloy, Naoise Mac Giollabhui, Amber A. Graham, Allison Stumper, Corinne P. Bart, Erin E. Curley, Laura E. McLaughlin, Daniel P. Moriarity, and Tommy H. Ng -- Schizophrenia spectrum and other psychotic disorders / Matilda Azis, Ivanka Ristanovic, Andrea Pelletier-Baldelli, Hanan Trotman, Lisa Kestler, Annie Bollini and Vijay A. Mittal -- Personality disorders / Cristina Crego and Thomas A. Widiger -- Sexual dysfunctions and paraphilic disorders / Jennifer T. Gosselin & Michael Bombardier -- Somatic symptom and related disorders / Michael J. Zvolensky, Lorra Garey, Justin Shepherd, and Georg H. Eifert -- Dissociative disorders / Steven Jay Lynn, Scott O. Lilienfeld, Harald Merckelbach, Reed Maxwell, Damla Aksen, Jessica Baltman, and Timo Giesbrecht -- Substance-related and addictive disorders / Keith Klostermann, Michelle L. Kelley, and Sarah Ehlke -- Mental health and aging: -- Amy fiske, ruifeng cui, & alexander ebert -- Common problems of childhood and adolescence -- Externalizing disorders of childhood and adolescence / Eva R. Kimonis, Paul J. Frick, and Georgette E. Fleming -- Internalizing disorders of childhood and adolescence / Janay B. Sander, Lindsay K. Rye, and Thomas H. Ollendick -- Learning disorders of childhood and adolescence / Rebecca S. Martinez and Leah M. Nellis -- Eating disorders / Danielle E. MacDonald, Traci McFarlane, and Kathryn Trottier -- Gender dysphoria / Jennifer T. Gosselin & Michael Bombardier -- Autism spectrum disorders / Susan W. White & Caitlin M. Conner.
Revised edition of Psychopathology, 2016.
OCLC-licensed vendor bibliographic record.
Keywords: Psychology, Pathological; PSYCHOLOGY / Psychopathology / General; PSYCHOLOGY / Clinical Psychology; MEDICAL / Mental Health